2016
DOI: 10.1262/jrd.2016-047
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin increases developmental competence of mouse embryos <i>in vitro</i> by inhibiting cellular apoptosis and modulating <i>HSP70</i> and DNMT expression

Abstract: Scutellaria baicalensis has been effectively used in Chinese traditional medicine to prevent miscarriages. However, little information is available on its mechanism of action. This study is designed specifically to reveal how baicalin, the main effective ingredient of S. baicalensis, improves developmental competence of embryos in vitro, using the mouse as a model. Mouse pronuclear embryos were cultured in KSOM medium supplemented with (0, 2, 4 and 8 μg/ml) baicalin. The results demonstrated that in vitro cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…When compared with in vivo conditions, the mouse embryo quality and blastocyst development rate are significantly decreased when cultured in vitro. The addition of Baicalin significantly improved the development ability of mouse embryos in vitro, which was associated with the effects of inhibiting apoptosis and reducing cellular stress by Baicalin [ 32 ]. Guo et al (2019) found that Baicalin could inhibit the production of ROS, reduce oocyte apoptosis, and improve the maturity of porcine oocytes and subsequent embryonic development in vitro [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with in vivo conditions, the mouse embryo quality and blastocyst development rate are significantly decreased when cultured in vitro. The addition of Baicalin significantly improved the development ability of mouse embryos in vitro, which was associated with the effects of inhibiting apoptosis and reducing cellular stress by Baicalin [ 32 ]. Guo et al (2019) found that Baicalin could inhibit the production of ROS, reduce oocyte apoptosis, and improve the maturity of porcine oocytes and subsequent embryonic development in vitro [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthremore, baicalin exhibited embryo-protection (Qi et al. 2016), weight losing (Yun and Jung 2014), sleep–wake regulation (Chang et al. 2011), anti-allergic (Kim et al.…”
Section: Pharmacological Activities Of Extracts and Major Compoundsmentioning
confidence: 99%
“…It can also improve lung function 6 and fertility 7 .The most common mechanism of Baicalin being against pathogenesis is its protective effect by reducing the production of oxidative stress 8 . Interestingly, Qi et al 9 reported that Baicalin could enhance the developmental competence of mouse embryos through suppressing cellular apoptosis and HSP70 expression, and activating DNA methylation. However, whether or not Baicalin can prevent malformation of the cardiovascular system caused by environmental hazards at an early stage remains unclear.…”
Section: Introductionmentioning
confidence: 99%